Spatial orientations of angular momentum vectors of galaxies in Supercluster S [173+014+0082] - Malla, Janak Ratna; Saurer, Walter; Aryal, B (BIBECHANA, 2021)
The spin vector orientation of 1302 SDSS (Sloan Digital Sky Survey) galaxies in Supercluster S[173+014+0082] having redshift 0.076 to 0.091 has been analyzed. The positions, position angles, and inclination angles of galaxies are used to convert two-dimensional observed parameters into three-dimensional angular momentum vectors of the galaxy using the `position angle-inclination' method. The expected isotropic distribution curves are determined by performing numerical simulation by generating 107 virtual galaxies. The observed distribution is compared with the expected isotropic distribution curves using three statistical tools namely Chi-square test, autocorrelation test, and Fourier test. Redshift map is studied and found that the distributions fit with the Gaussian. No preferred alignment of angular momentum vectors is noticed, supporting the Hierarchy model of galaxy formation.BIBECHANA 18 (1) (2021) 26-32